2020
DOI: 10.3390/pharmacy8010043
|View full text |Cite
|
Sign up to set email alerts
|

Oncology Pharmacists Can Reduce the Projected Shortfall in Cancer Patient Visits: Projections for Years 2020 to 2025

Abstract: Based on the projected need for a larger oncology care workforce, we estimated the patient care visits and care activities that Board Certified oncology pharmacists (BCOPs) could contribute to oncology care from 2020–2025. Using projected counts for BCOPs through 2025, we estimated that 2.9–4.1 million 30-min BCOP patient visits were possible at 50% workforce capacity. BCOPs’ clinical activities overlapped strongly with those of nurse practitioners (NPs) and physician assistants (PAs) in patient education and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…A variety of studies echoed the role of pharmacists in leading the implementation of pharmacogenomics within their work settings [ 67 , 68 , 69 , 70 , 71 , 72 ]. Given the United Arab Emirates’ endeavors to follow a multidisciplinary approach for project implementation, ensuring harmony, commitment, and unity, including a large variety of healthcare worker specialties in our cohort was very important [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies echoed the role of pharmacists in leading the implementation of pharmacogenomics within their work settings [ 67 , 68 , 69 , 70 , 71 , 72 ]. Given the United Arab Emirates’ endeavors to follow a multidisciplinary approach for project implementation, ensuring harmony, commitment, and unity, including a large variety of healthcare worker specialties in our cohort was very important [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the demand for oncology services is steadily increasing, there is a projected shortage of oncology practitioners to address the demand. 36 Considering the cornerstone of supportive care and symptom management is pharmacotherapy, this provides an opportunity to elevate the pharmacist's role on the multidisciplinary team to further assist oncology practitioners to optimize patient health outcomes. Clinical pharmacists, including those with specialized training in oncology, are expertly trained to provide a plethora of services to cancer patients, including medication reconciliation, preparation and dispensing of chemotherapy, assisting in mitigating financial toxicity incurred by patients, monitoring drug‐drug and drug‐disease interactions, and providing patient education on medications.…”
Section: Discussionmentioning
confidence: 99%
“…Role of the clinical pharmacist in addressing disparities with the use of SCM among minority patient populationsWhile the demand for oncology services is steadily increasing, there is a projected shortage of oncology practitioners to address the demand 36. Considering the cornerstone of supportive care and symptom management is pharmacotherapy, this provides an opportunity to elevate the pharmacist's role on the multidisciplinary team to further assist oncology practitioners to optimize patient health outcomes.…”
mentioning
confidence: 99%
“…Regarding capacity, the study by Shih et al identified 1,090 oncology pharmacists in 2019 while citing a 2014 estimate from ASHP of 1,863 BCOPs 6 (this 2014 estimate included non-US BCOPs). Meanwhile, a recent growth trend study by Knapp and Ignoffo 7 identified 2,761 US-based BCOPs in 2019. At the end of 2020, BPS records showed 3,074 BCOPs (data provided by BPS staff in January 2021).…”
mentioning
confidence: 99%